THE IMPLEMENTATION OF AHRD IN INDONESIA STUDY CASE: HUMAN RIGHTS VIOLATIONS TOWARDS HUMAN RIGHTS ACTIVISTS IN PAPUA - Iron Nur Biantoro; Siti Athiya Alifah; Putri Dira Fahira (Sociae Polites, 2022)
Cases of human rights violations continue to occur in the Asian region, including the ASEAN region, even though ASEAN countries have agreed to adopt the ASEAN Human Rights Declaration. In fact, the practice of AHRD is still minimally considered by ASEAN and ASEAN members themselves. Indonesia as an ASEAN member is also still taking action against human rights such as the case in Papua, not only local residents who get human rights violations from the government, but also from some data it is found that Papuan human rights activists are also intimidated. In this case, it can be seen that the implementation of the AHRD has not been fully maximized in Indonesia in handling cases of human rights violations contained in the points in the AHRD.